Jornalismo e imaginário: a simbologia da seca - Costa, Maria Tatiana Lima (2020)
The imaginary is a river that crosses time, gains strength, dominance, power and visibility when flows into its afluents in abundance. From this perspective, the present study seeks to make an observation on the connection between journalism and imaginary happenings. To do so, starting from a symbolic perspective, we studied the imagery of drought in the journalistic field, using it as an object of analysis the “Agreste Seco” report series, published on November 27, 2016, by JC Online, news website of Jornal do Comercio do Estado de Pernambuco. From the analysis of the corpus, composed entirely of 25 narratives and 13 images, the research identified how verbal and non-verbal elements function as devices from which the newspaper presents as imagery of drought to the reader. As for the approach, the methodological path adopted a study based on the General Theory of the Imaginary, through which it was especially outworked with Symbolic Hermeneutics (HS), a method through which Gilbert Durand (2001) establishes an anthropological structure to identify the manifestation of the imaginary symbols evoked, in this case, narrative and journalistic image. From the symbology, that is, from the symbolic set present in the series, we identified that JC Online presents the “tragic imagery of drought”, directing the reader's vision towards the tragic, the fall, the anguish, the discouragement, the sadness, the situation of darkness, painful experiences, chaos, among other sensations that signal the presence of the imaginary diurnal regime.